Pedal force effectiveness in cycling: a review of constraints and training effects - Bini, R. R.; Hume, P. A.; Croft, J.; Kilding, A. E. (Journal of Science and Cycling, 2013)
Pedal force effectiveness in cycling is usually measured by the ratio of force perpendicular to the crank (effective force) and total force applied to the pedal (resultant force). Most studies measuring pedal forces have been restricted to one leg but a few studies have reported bilateral asymmetry in pedal forces. Pedal force effectiveness is increased at higher power output and reduced at higher pedaling cadences. Changes in saddle position resulted in unclear effects in pedal force effectiveness, while lowering the upper body reduced pedal force effectiveness. Cycling experience and fatigue had unclear effects on pedal force effectiveness. Augmented feedback of pedal forces can improve pedal force effectiveness within a training session and after multiple sessions for cyclists and non-cyclists. No differences in pedal force effectiveness were evident between summarized and instantaneous feedback. Conversely, economy/efficiency seems to be reduced when cyclists are instructed to improve pedal force effectiveness during acute intervention studies involving one session. Decoupled crank systems effectively improved pedal force effectiveness with conflicting effects on economy/efficiency and performance.